Association Between Maternal Use of Smart Bracelets and Stunting Incidence in Toddlers: A Case-Control Study in Sumedang, Indonesia - Apriany, Dyna; Zahrah, Rinjani Cikal Annisa; Nurjanah, Nunung (Universitas Pendidikan Indonesia, 2025)
Introduction: Stunting remains a significant public health issue in Indonesia, particularly in rural areas such as Sumedang, West Java. Maternal health during pregnancy is a critical determinant of fetal growth, yet limited attention has been given to digital health innovations as part of stunting prevention strategies. Objective: This study aimed to examine the association between maternal use of smart bracelets during pregnancy and the incidence of stunting in toddlers, while also assessing the influence of maternal education, antenatal care (ANC) attendance, and dietary intake. Methods: A case-control study was conducted in Margamukti Village, Sumedang Regency, involving 100 mother-child pairs (50 cases and 50 controls). Data were collected through structured interviews and cross-referenced with maternal and child health records. Statistical analyses included chi-square tests, odds ratio (OR) calculations, and multivariate logistic regression to identify factors independently associated with stunting. Results: Mothers in the control group (non-stunted children) reported higher use of smart bracelets during pregnancy (56%) compared to the case group (24%). Smart bracelet use was significantly associated with reduced odds of stunting (adjusted OR = 0.28, 95% CI: 0.12–0.64, p = 0.003). Other protective factors included higher maternal education (adjusted OR = 0.46, 95% CI: 0.21–0.98, p = 0.045), attending ≥4 ANC visits (adjusted OR = 0.35, 95% CI: 0.16–0.78, p = 0.009), and adequate dietary intake during pregnancy (adjusted OR = 0.31, 95% CI: 0.14–0.68, p = 0.005). Conclusion: Smart bracelet use during pregnancy is a promising digital health intervention that may contribute to reducing the risk of stunting in toddlers. These findings support the integration of wearable technologies alongside traditional maternal health strategies, particularly in resource-limited settings. Strengthening maternal education, nutrition, and ANC coverage remains essential for comprehensive stunting prevention.